Peopling for profit in imperial Brazil directed migrations and the business of nineteenth-century colonization - Pérez Meléndez, José Juan (Cambridge Latin American studies, 2024)
Peopling for Profit provides a comprehensive history of migration to nineteenth-century imperial Brazil. Rather than focus on Brazilian slavery or the mass immigration of the end of the century, José Juan Pérez Meléndez examines the orchestrated efforts of migrant recruitment, transport to, and settlement in post-independence Brazil. The book explores Brazil's connections to global colonization drives and migratory movements, unveiling how the Brazilian Empire's engagement with privately run colonization models from overseas crucially informed the domestic sphere. It further reveals that the rise of a for-profit colonization model indelibly shaped Brazilian peopling processes and governance by creating a feedback loop between migration management and government formation. Pérez Meléndez sheds new light on how directed migrations and the business of colonization shaped Brazilian demography as well as enduring social, racial, and class inequalities. This title is part of the Flip it Open programme and may also be available Open Access. Check our website Cambridge Core for details